Magnetic resonance imaging patterns of Viral Encephalitis: A pictorial narrative review - Varshney, Sumedha; Ranjan, Rahul; Deo, Namrata; Pandey, Nirmal; Rajput, Jaisingh; Kumar, Shashikant (Nepal Journal of Neuroscience, 2025)
Viral encephalitis is the infection of brain parenchyma caused by severalgroups of viruses. It can involve any age group and usually presents with the general symptoms of fever, headache, seizure, neurological deficit, or altered sensorium. However; few viruses can produce a specific group of systemic symptoms that can help to distinguish them from other causes. The two most important tools for determining the etiology of a disease are CSF examination and polymerase chain reaction (PCR). Furthermore, neuroimaging plays a critical role in diagnosing encephalitis, the direction and pattern of spread of the causative organism and the complications. In this pictorial essay, the various types of viral encephalitis are discussed along with their imaging pattern.